Comparison of Two Techniques of Measuring Activated Clotting Time During Cardiac Surgery - Alam, Waqas; Hussain, Syed Aqeel; Ali, Muhammad; Akram, Muhammad Adnan; Farooq, Muhammad Umar; Masroor, Rehan; Khalil, Hafsa; Sana, Ayesha (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare two techniques of activated clotting time (ACT) measurement by two different devices to evaluate the correlation and agreement between these techniques at different points of time during cardiac surgery.Study Design: Comparative Cross-sectional Study.Study settings: Cardiac Anesthesia Department, Armed Forces Institute of Cardiology and National Institute of Heart Diseases, Rawalpindi Pakistan, from Feb 2022 to Apr 2022.Methodology: 100 patients undergoing CABG surgery on pump were included by non-probability consecutive sampling technique. Two devices operating on different techniques of measurement were used to measure ACT at four different points of time during surgery. Same sample was used to measure ACT from both devices. Data was collected and analysed by SPSS V.20.0. Pearson's chi square test and paired sample t-test were applied to measure the significance. Linear regression analysis was done to find correlation and Bland Altman plot was used for checking agreement between ACT values from both devices.p-value less than 0.05 was considered significant.Results: Out of 100, male patients were 79 and female patients were 21. Their mean age was 54.18±11.91 years and mean weight was 79.06±18.49 kg. Moderate positive correlation was found with Pearson r value of 0.55. There was poor agreement between the ACTs measured by two devices. On average Hem R measures ACT 63.54±50.83 seconds higher than Hem JSP. Average mean and median values for Hem R group are 400.03±59.39 sec and 397.75sec respectively and for Hem JSP group are 336.49±44.63 sec and 340.5 sec respectively.Conclusion: There is moderate positive correlation but poor agreement between the values of ACT measured by Hem R and Hem JSP due to different techniques of measurement so these should not be used interchangeably.